Klasifikasi Model Percakapan Twitter Mengenai Ujian Nasional - Emilya Ully Artha; Ahmad Dahlan (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
The rise of internet usage especially in social media such as Twitter make a possibility to analyze an existing conversations and derived it to various conversation theme. The data was obtained from the Twitter conversation using text mining that is a "national exam" using the National #ujian, #unas, and #ujianan hastags. Twitter API was used to extract tweet data. This research use the naive bayesian access method to view communication forms based on users and applications. Based on calculation this research obtain a 0.278 result that most of Twitter users (users) are being from @kabarDiknas. The data that used in this research are taken from is a twitter conversation about the “ujian nasional” in 2016.